2020
DOI: 10.1159/000509639
|View full text |Cite
|
Sign up to set email alerts
|

Further Analytical, Pharmacokinetic, and Clinical Observations on Low-Dose Ponatinib in Patients with Philadelphia Chromosome-Positive Acute Lymphoblastic Leukemia

Abstract: Introduction: Ponatinib (PNT) is a tyrosine kinase inhibitor approved for treating patients with Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph + ALL), or chronic myeloid leukemia, resistant or intolerant to other tyrosine kinase inhibitor or showing T315I mutation of BCR-ABL. Unfortunately, the clinical use of PNT is limited by the possible occurrence of vascular occlusive events. The incidence of vascular events seems to correlate with PNT dose intensity and plasma exposure. Dose reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Stock concentrations were 20 mM for DASA, IMA and PONA, and 3 mM for NILO, respectively. Peak and IC 50 concentrations were chosen according to the literature: DASA 150 nM (peak) and 10 nM (IC 50 ); IMA 3000 nM (peak) and 600 nM (IC 50 ); NILO 3000 nM (peak) and 30 nM (IC 50 ); PONA 145 nM (peak) and 70 nM (IC 50 ) (Peng et al 2004 ; Kantarjian et al 2006 , 2010 ; Rix et al 2007 ; Weisberg et al 2007 ; Cortes et al 2012 ; Menna et al 2020 ). Direct effects of DMSO (maximum level was 0.1% v/v in NILO peak samples) were ruled out by including DMSO only as control throughout all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Stock concentrations were 20 mM for DASA, IMA and PONA, and 3 mM for NILO, respectively. Peak and IC 50 concentrations were chosen according to the literature: DASA 150 nM (peak) and 10 nM (IC 50 ); IMA 3000 nM (peak) and 600 nM (IC 50 ); NILO 3000 nM (peak) and 30 nM (IC 50 ); PONA 145 nM (peak) and 70 nM (IC 50 ) (Peng et al 2004 ; Kantarjian et al 2006 , 2010 ; Rix et al 2007 ; Weisberg et al 2007 ; Cortes et al 2012 ; Menna et al 2020 ). Direct effects of DMSO (maximum level was 0.1% v/v in NILO peak samples) were ruled out by including DMSO only as control throughout all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Peak and IC50 concentrations were chosen based on clinical studies which reported serum levels in patient samples. Peak levels as well as steady-state concentrations (from here on: IC50) were based on these data [20][21][22][23][24][25][26][27]. The concentrations were chosen as follows: ASCI 806 nM (peak) and 28 nM (IC50); BOSU 600 nM (peak) and 2.4 nM (IC50); DASA 150 nM (peak) and 10 nM (IC50); IMA 3000 nM (peak) and 600 nM (IC50); NILO 3000 nM (peak) and 30 nM (IC50); PONA 145 nM (peak) and 70 nM (IC50).…”
Section: Tyrosine Kinase Inhibitors (Tki)mentioning
confidence: 99%
“…A be useful. Therapeutic windows of 1000-1100 to 3000 ng/ml for imatinib (28)(29)(30), 50 to 100 ng/ml for sunitinib (23,24), 20 to 46-50 ng/ml for pazopanib (25)(26)(27), have been proposed on the basis of TDM.…”
Section: Tdm For Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Ponatinib was approved at the dose of 45 mg/day, which resulted in plasma concentrations significantly higher than those associated with antileukemic activity (40 nM): however, ponatinib caused serious cardiovascular toxicity when used at this dose level (28). Continued TDM may allow for reducing ponatinib dose to 15-30 mg/day, with this regimen causing plasma concentrations of approximately 40 nM while also reducing risk of cardiovascular events (29,30).…”
Section: Tdm For Tyrosine Kinase Inhibitorsmentioning
confidence: 99%